Correlations between Humoral Immunity, Vaccination Period and Demographic Characteristics of First Immunized Smallpox Vaccine Recipients - O. S. Ermilova; Z. I. Ghinko; V. A. Belyavskaya (Эпидемиология и вакцинопрофилактика)
Relevance. After vaccination against smallpox is completed, more than 50% of the population are not immune to pathogens of the genus Orthopoxvirus, which creates the risk of mass infection if the smallpox virus is used as a biological weapon.Aim. To assess the correlations between humoral immunity, clinical signs during a vaccination period and, sex and age characteristics of vaccinia virus Practical Aspects of Epidemiology and Vaccine Prevention (VCV) recipients.Materials and methods. We studied a vaccination clinical data of 82 subjects first vaccinated with a smallpox vaccine. Vaccinia neutralizing antibody titers were determined for 27 subjects using plaque reduction neutralization tests. According to antibody titers they were divided into groups of mild (25%), moderate (50%), and heavy reaction (25%).Results. A total of 34% and 66% vaccine recipients experienced mild or moderate vaccination period, respectively. Among them 83% vaccine recipients experienced or local and systemic adverse events. Compared to mild group, moderate group had larger scab, hyperemia (p < 0,01) and pustules (p < 0,05). It was a tendency that men had smaller scabs, more rapid scab shedding and less intense hyperemia compared to women. In contrast to low and high neutralizing antibody titers, medium ones were associated with smaller local inflammation (induration zones, hyperemia, pustules).Conclusion. The same vaccine and vaccination schedule may produce different protective neutralizing antibody levels and different humoral immunity in similar demographic groups. The underlying reasons need further research.